The Influence of Advertising on Consumer Behavior - Probstnerová, Laura (2017)
The purpose of this study was to analyze, how different factors have an influence on consumer behavior and their decision making. In the theoretical part, advertising as a part of commercial communication is discussed, along with consumer behavior and the decision making process, namely factors that influence it, such as social, personal and psychological. Further, the psychology of advertisement is described in terms of brand, its equity and measures affecting the brand preference, and how does a brand create artificial needs. The empirical part is based on the analysis of a brand Apple. Closer look is taken at its identity and marketing strategy, as well as some examples of advertising. The empirical part includes own research based on data collected from self administered survey, concerning the smartphone brand preference among consumers. It is focusing specifically on Apple and its biggest rival, Samsung. The findings showed, that a brand with higher brand equity in the form of brand awareness and identity will be preferential in the purchase decision making process, especially among Millennials, which in this case turned out to be Apple.